A mucosal recovery software tool for endoscopic submucosal dissection in early gastric cancer - Zhao, Yinuo; Wang, Huogen; Fan, Yanyan; Jin, Chaohui; Xu, Qinwei; Jing, Jiyong; Zhang, Tianqiao; Zhang, Xuedong; Chen, Wanyuan (Frontiers in Medicine, 2022)
Due to the limited diagnostic ability, the low detection rate of early gastric cancer (EGC) is a serious health threat. The establishment of the mapping between endoscopic images and pathological images can rapidly improve the diagnostic ability to detect EGC. To expedite the learning process of EGC diagnosis, a mucosal recovery map for the mapping between ESD mucosa specimen and pathological images should be performed in collaboration with endoscopists and pathologists, which is a time-consuming and laborious work. This article introduces a mucosal recovery software tool “Pathology Helper” for the construction of mucosal recovery maps. We proposed the improved U-Net to obtain WSI-level segmentation results, and the WSI-level results can be mapped to the macroscopic image of the specimen. With the help of “Pathology Helper”, we can construct the high-quality mucosal recovery maps to reduce the workload of endoscopists and pathologists. Our work can also improve the detection rate of early gastric cancer, so that more patients with gastric cancer can get timely treatment.